Line Intensity Measurements of the ν7+ν8 Band of Ethylene (12C2H4). (10th July 2013) - Lebron, G. B.; Tan, T. L.
Abstract : From the four high-resolution FTIR absorbance spectra recorded at a spectral resolution of 0.0063 cm −1, 123 line intensities belonging to theν 7 + ν 8 band of 12 C2 H4 were measured and fit. The upperv 7 + v 8 = 1 state rovibrational constants up to sextic terms determined using a Watson'sA -reduced Hamiltonian model inI r representation were used to calculate the line intensities of the band. Results of the experimental fit of the line intensities agree well with those obtained by calculations.